MENGUJI FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT VAKSINASI HALAL COVID-19 MASYARAKAT MUSLIM - Zaid, Zaid; Al Bahy, Mahbub Pasca (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Covid-19 outbreak, which is considered to be still not optimal enough, the Indonesian government seems to be risking its efforts on a mandatory vaccination policy. However, this intervention will not succeed without the participation of the community in the form of their interest in receiving the Covid-19 vaccination. Therefore, by involving 422 Muslim respondents who live in the Special Region of Yogyakarta, the main objective of this study is to focus on the factors that influence or predict halal Covid-19 vaccination intention. Thus, it is clear that this research is a quantitative descriptive study with a cross-sectional survey. The results of the descriptive analysis of this study then explained that the majority of respondents were Muslim people who were male as much as 217 (51.42%), aged 19 - 24 years (38.39%), domiciled in the city of Yogyakarta (38.63%) and worked as students as many as 188 people (44.55%). While the results of quantitative analysis using the Partial-least square structural equation modeling (PLS-SEM) method in this study revealed that halal Covid-19 vaccination intention was influenced by factors such as attitude toward halal vaccination (β = 0.541, t-value = 10.199, -value = 0.000), subjective norm (β = 0.196, t-value = 3.913, -value = 0.000), and social norm (β = 0.156, t-value = 3.374, -value = 0.001) positively and significant. In addition, the theoretical and practical implications based on the results of the research are also discussed in this study.